A straightforward and versatile FeCl3 catalyzed Friedel–Crafts C-glycosylation process. Application to the synthesis of new functionalized C-nucleosides. (21st March 2019) - Tachallait, Hamza; Safir Filho, Mauro; Marzag, Hamid; Bougrin, Khalid; Demange, Luc; Martin, Anthony R.; Benhida, Rachid
Abstract : Rapid and straightforward access to C -nucleosides using an inexpensive FeCl3 catalyst. Abstract : A new, straightforward and eco-compatible route to C -(hetero)aryl nucleosides is reported. This ribosylation process consists of a one-step FeCl3 catalyzed Friedel–Crafts β- C -glycosydation reaction. This reaction occurs through an oxonium intermediate from readily available protected sugars leading to functionalized C -nucleosides with high stereocontrol. The expected new C -nucleosides were obtained in good yields within a short reaction time (10 min). Moreover, this approach is compatible with the use of a range of bulky (poly)aromatics such as naphthalene, anthracene and pyrene, which are not easily accessible via classical routes. These new C -aryl-nucleosides exhibit interesting photophysical properties, underling their potential use for further nucleic acid labelling.